MENINGKATKAN HASIL BELAJAR IPS SISWA PADA KONSEP PERUBAHAN LINGKUNGAN MELALUI MODEL KOOPERATIF TIPE TALKING STICK SD NEGERI 2 BUNGI - Safiuddin Safiuddin (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2018)
This Research aim to to know ability of relevant student with method instruction of teacher [pass/through] study of co-operative of type Talking Stick. this Desain Research experiment kuasi with device of red design group control pretest-posttest. Technique intake of sampel in this random sampel. Sampel in this research class of IV amounting to 33 student. Technique data collecting which [in] using in method of Speaking that is in the form of Talking Stick.